Perceived Work Stress on the Performance of the Hospital Nurses During Covid-19 Pandemic: Is Intrinsic Motivation a Moderator Variable - Tobing, Fenny; Anggraini, Nenny; Silvanita, Ktut; Saragih, Lasni (Advances in Social Sciences Research Journal, 2022)
The nursing profession is known as the backbone of the health sector. They are required to provide optimal service and are expected to get no complaints from the patients. That demand often makes nurses feel stress (perceived work stress) on their duty, therefore will affect their performance. Nurses’ perceived work stress was getting higher when Covid-19 hit the world. Increased workload, a chaotic work environment, and a lack of nurses cause work stress and can negatively affect the performance of nurses. This study uses quantitative methods to examine and analyze the effect of perceived work stress on the performance of nurses with intrinsic motivation as a moderator variable. This research was conducted by distributing questionnaires to a number of nurses at ’RS-X’ Hospital in East Jakarta, Indonesia. Hypothesis testing is done by regression analysis using SPSS 25. The results showed that perceived work stress had a negative effect on nurse performance. The addition of the intrinsic motivation variable in the model increases the R-square value, but this variable does not moderate (weaken or strengthen) the effect of perceived work stress on nurse performance.